Revealing the Effects of Trace Oxygen Vacancies on Improper Ferroelectric Manganite with In Situ Biasing. (18th January 2019) - Cheng, Shaobo; Meng, Qingping; Han, Myung‐Geun; Deng, Shiqing; Li, Xing; Zhang, Qinghua; Tan, Guotai; Botton, Gianluigi A.; Zhu, Yimei
Abstract: Multiferroic materials, which exhibit multiple orderings, are promising for next generation data‐storage device applications. YMnO3, in particular, because of the coexistence of the ferroelectricity and (anti)ferromagnetism within one single material, has drawn special attentions to application‐based research. However, the role of defect chemistry related to the behaviors of the ferroelectric polarization has been seldomly studied due to its complexity. In this work, a novel switching behavior of multiferroic YMnO3 single crystal is reported using in situ biasing and Landau based numerical calculation. It is revealed that the domain switching only happens at the topmost surface, which can be well explained by the electric field redistribution due to the trace amount of oxygen vacancies. These in situ observations demonstrate that defect chemistry plays an important role in domain switching and can be utilized as an additional parameter for controlling the distribution of electric field within the multiferroic materials. Abstract : The effects of trace oxygen vacancies are revealed on switching behaviors in multiferroic YMnO3 single crystal using in situ biasing and Landau based numerical calculations. The domain switching only occurs near the topmost surface area under different electric fields, which can be attributed to the electric field redistribution induced by the oxygen vacancies.